New European Union’s Regulatory Framework of the Digital Space: the Digital Markets Act and the Digital Services Act - Kalėda, Saulius Lukas (Teisė, 2023)
With the adoption of two regulations in 2022, the Digital Markets Act (DMA) and the Digital Services Act (DSA), the European Union completed its digital services regulatory reform aimed at laying down horizontal rules applicable to the key providers of information society services, including large online platforms. Based on the legislative history, existing case law and the unfolding legal doctrine, this article examines links between the two legal instruments, key aspects of the new regulatory framework, as well as selected legal issues relating to its future application. All opinions expressed in this article are author’s personal views.
Keywords: European Union law; protection of fundamental rights; competition law; digital services; online platforms